2018
DOI: 10.1002/hlca.201700273
|View full text |Cite
|
Sign up to set email alerts
|

Selective Encapsulation and Enhancement of the Emission Properties of a Luminescent Cu(I) Complex in Mesoporous Silica

Abstract: We describe a synthetic approach to prepare new luminescent silica‐based materials through the encapsulation of a neutral copper(I) complex inside the pores of mesoporous silica nanoparticles (MSN). The copper(I) complex is present, in the solid state, as two polymorphs, blue and yellow emissive, and in solution it shows a pale yellow color that is also mirrored by an emission in the yellow‐orange region of the electromagnetic spectrum. The X‐ray structures of single crystals have been obtained for both polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The non-intense broad absorptions also have been observed in the longer wavelength region (>350 nm). These bands are attributed to the MLCT transition from the Cu(I) ion to the diimine ligand [29][30][31][32][33][34][35][36][37].…”
Section: Photophysical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-intense broad absorptions also have been observed in the longer wavelength region (>350 nm). These bands are attributed to the MLCT transition from the Cu(I) ion to the diimine ligand [29][30][31][32][33][34][35][36][37].…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…[28]. The high efficiency of photoluminescence and the potential for creating solution-processed organic light-emitting diodes have been shown [29][30][31][32][33][34][35][36][37]. On the example of complexes of pyridine-triazole with bis(diphenylphosphino)ferrocene, Chan and Chi et al have shown the possibility of the formation of both neutral (with ligand in a deprotonated form) and cationic complexes depending on the substituents in a heterocycle [38].…”
Section: Introductionmentioning
confidence: 99%
“…In general, a way to stabilize transition metal complexes ( i.e., preventing oxidation and distortion) can be performed by their encapsulation inside porous nanocontainers. For instance, the successful insertion of transition metal complexes inside mesoporous silica nanoparticles was already performed by De Cola et al , Costa et al and Hofkens et al , using Ir(III) ( de Barros e Silva Botelho et al, 2011 ; Ezquerro et al, 2019 ) Pt (II) ( Atoini et al, 2018 ) and Cu(I)complexes ( Donato et al, 2018 ) and Ag(I) clusters. ( Fenwick et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…35−37 Carbon-nanotubes have been used to modulate the assembly state of ionic liquids and lipids inside the cavity. 38,39 Mesoporous silica particles have been extensively investigated for the assembly of lipids, 40 surfactants, 41 dyes, 42 metal complexes, 43,44 and charge-transfer systems. 45 However, all of these examples focused on how small molecules arrange when entrapped into a confined space, but to the best of our knowledge, there is no report on how a nanoconfined space modifies the complex self-assembly pathways of supramolecular aggregates.…”
Section: ■ Introductionmentioning
confidence: 99%